Wide-temperature electrolyte and preparation method and application thereof
By introducing deep eutectic solutions formed by alcohols and amides into the electrolyte of aqueous zinc ion batteries, the problems of battery failure and dendrites in extreme temperatures are solved, and the high cycle stability and long life of the battery are achieved.
Patent Information
- Application Number
- CN202510107738.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-03-14
AI Technical Summary
The failure of aqueous zinc ion batteries under extreme temperature conditions and uncontrolled dendritic growth leads to a decrease in battery capacity and shortened service life.
Alcohol and amide substances are used to form deep eutectic solution as electrolyte additives. Through hydrogen bond complexing and ternary eutectic effect, the hydrogen bond network of the electrolyte is changed, and the activity of water and the formation of dendrites are inhibited.
The temperature range of the electrolyte is widened, the cycle stability and electrochemical performance of zinc ion batteries are improved, and the service life of the battery is extended.
Smart Images

Figure CN119627268A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous zinc ion batteries and electrolytes thereof, and in particular to a wide-temperature electrolyte and a preparation method and application thereof. Background Art
[0002] In recent years, lithium-ion batteries (LIBs) have been widely used in portable electronics due to their high energy density and are being considered for use in electric vehicles and large-scale energy storage systems. However, increasing concerns about cost, safety, limited lithium resources, and environmental impact have prompted the search for alternative battery systems. Compared with traditional organic electrolyte-based lithium-ion batteries, aqueous electrolytes have the advantages of greater safety, lower cost, and higher ionic conductivity, and have broad application prospects in large-scale energy storage. Among various aqueous metal ion batteries, rechargeable aqueous zinc ion batteries (ZIBs) have attracted widespread attention in future energy storage devices due to their high safety, low cost, abundant resources, and environmental friendliness.
[0003] In aqueous zinc-ion batteries, the negative electrode material is zinc foil, which has a low redox potential (-0.76 V vs. SHE) and a theoretical mass specific capacity of up to 820 mAh g -1 , volumetric capacity up to 5855mAh cm -3 . However, the formation of zinc dendrites, the decomposition of the electrolyte, and the production of byproducts covering the zinc anode can cause the capacity of zinc-ion batteries to decrease or even fail during the cycle. In addition, under extreme conditions such as high and low temperatures, the instability of the physical and chemical properties of the electrolyte further increases the possibility of zinc dendrite formation. Under high temperature conditions, various side reactions inside the battery will be enhanced, seriously affecting the battery life. Under low temperature conditions, the reduction of ionic conductivity, the freezing of water, and the precipitation of solid salts in the electrolyte hinder the transport of ions, making it difficult for zinc ions to deposit evenly, thereby increasing the risk of zinc dendrite formation. In order to solve the adverse effects of extreme temperature conditions on aqueous zinc-ion batteries, researchers have studied a variety of strategies from the perspective of electrolytes, including the use of high-concentration salt electrolytes and gel electrolytes as well as electrolyte additives. Among these strategies, the introduction of additives into the electrolyte is considered to be a simple and effective method, but currently only a very small number of electrolyte additives have been proven to be effective in expanding the operating temperature of the battery.
[0004] Therefore, it is of great practical significance to develop additives with a wider temperature range, stable zinc anode performance, higher safety and lower cost. Summary of the invention
[0005] Based on this, the present invention provides a method for preparing a wide-temperature electrolyte to solve the problems of failure of existing aqueous zinc ion batteries under extreme conditions and uncontrolled dendrite growth.
[0006] To achieve the above object, on the one hand, the present invention provides a method for preparing a wide temperature range electrolyte, which comprises the following steps:
[0007] S1, mixing an alcohol substance as a hydrogen bond donor and an amide substance as a hydrogen bond acceptor at a molar ratio of 1:0.2-1:20, and heating them to complete the complexation, so as to prepare a deep eutectic solution; wherein the alcohol substance is selected from at least one of ethanol, ethylene glycol, and glycerol, and the amide substance is selected from at least one of caprolactam, formamide, and trifluoroacetamide;
[0008] S2. The deep eutectic solution is used as an electrolyte additive and mixed with deionized water, and zinc acetate is added to prepare a wide temperature electrolyte.
[0009] As a further preferred technical solution of the present invention, in step S1, the temperature for heating the complexation reaction is 50-90°C.
[0010] As a further preferred technical solution of the present invention, in step S1, the alcohol substance and the amide substance are mixed in a molar ratio of 1:2.
[0011] As a further preferred technical solution of the present invention, in step S2, the deep eutectic solution is added to deionized water at a volume percentage of 20-80%.
[0012] As a further preferred technical solution of the present invention, the concentration of zinc acetate in the wide temperature range electrolyte is 0.2-4 mol / L.
[0013] According to another aspect of the present invention, the present invention also provides a wide temperature range electrolyte, which is prepared by the above method.
[0014] According to another aspect of the present invention, the present invention also provides an application of a wide temperature electrolyte in an aqueous zinc ion battery.
[0015] Compared with the prior art, the present invention can achieve the following beneficial effects:
[0016] 1) The present invention introduces a deep eutectic solution into the electrolyte as an additive of the electrolyte. The preparation operation of the electrolyte is simple, the conditions are controllable, and it is easy to mass produce. At the same time, the deep eutectic solution is low in price, green and environmentally friendly, and is an additive material with application potential;
[0017] 2) In the wide temperature electrolyte obtained by the present invention, specific alcohol substances and amide substances are selected to form a bond complex with each other, and both of them will form hydrogen bonds with water molecules at the same time to achieve a ternary eutectic effect, and then the hydrogen bonds between the deep eutectic solution and water are used to lock free water molecules, which can change the original hydrogen bond network in the solution. This can not only inhibit the activity of water and prevent the battery from forming dendrites due to side reactions under high temperature conditions, but also prevent the electrolyte from solidifying due to the stacking of six-membered rings similar to pure water under low temperature conditions, which can greatly reduce the freezing point of the electrolyte, thereby widening the temperature range of the electrolyte;
[0018] 3) In the wide-temperature electrolyte obtained by the present invention, the alcohol substances and the amide substances are bonded and complexed with each other to form a compound with a specific ring structure, and are adsorbed on the electrode interface of the zinc ion battery to form an electrolyte interface film. The ring structure has an ion channel with a specific function. Through steric hindrance and electrostatic interaction, the channel only allows zinc ions to be transported, and free water molecules are excluded from the SEI film. It can effectively induce uniform deposition of zinc, inhibit the formation of dendrites on the zinc electrode, alleviate side reactions such as corrosion, and effectively improve the electrochemical performance of the zinc ion battery.
[0019] 4) The wide temperature electrolyte of the present invention is applied to aqueous zinc ion batteries, so that the aqueous zinc ion batteries can still maintain a stable cycle for an extremely long time under extreme conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0021] Figure 1 The state comparison of different wide temperature electrolytes in Examples 1, 5, and 6 and the 1 mol / L zinc acetate electrolyte in Comparative Example 1 at -50°C is shown in the figure. From left to right, the electrolyte samples of Examples 1, 5, 6 and Comparative Example 1 are shown.
[0022] Figure 2 The wide temperature electrolyte of Example 1 is 1 mA / cm at 25°C. 2 The electrode surface and element distribution of zinc-ion battery after 10 cycles of current density.
[0023] Figure 3 The 1 mol / L zinc acetate electrolyte in Comparative Example 1 is 1 mA / cm 2 The electrode surface of the zinc ion battery after 10 cycles of current density.
[0024] Figure 4 The long cycle performance of the zinc-zinc symmetrical battery assembled with the wide temperature electrolyte in Example 1 and the 1 mol / L zinc acetate electrolyte in Comparative Example 1 at different temperatures (-50°C, 25°C, 50°C) is compared.
[0025] Figure 5 This is the long cycle performance of the blended electrolyte in Comparative Example 2 at different temperatures (-50°C, 25°C, 50°C).
[0026] Figure 6 The long cycle performance of the zinc-zinc symmetrical battery assembled with the wide temperature electrolyte in Example 5 and the 1 mol / L zinc acetate electrolyte in Comparative Example 1 at different temperatures (-50°C, 25°C, 50°C) is compared.
[0027] Figure 7 The long cycle performance of the zinc-zinc symmetric battery assembled with the wide temperature electrolyte in Example 6 and the 1 mol / L zinc acetate electrolyte in Comparative Example 1 at different temperatures (-50°C, 25°C, 50°C) is compared.
[0028] Figure 8 The long cycle performance of the zinc-zinc symmetrical battery assembled with the wide temperature electrolyte in Comparative Example 3 at different temperatures (-50°C, 25°C, 50°C).
[0029] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0030] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0031] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0032] Comparative Example 1
[0033] The specific preparation method of the additive-free zinc acetate electrolyte provided in this comparative example is as follows:
[0034] Dissolve 0.1 mol zinc acetate in 100 mL of deionized water and stir at room temperature to dissolve into a 1 mol / L zinc acetate electrolyte (Zn(OAc)2).
[0035] Comparative Example 2
[0036] The blended electrolyte provided in this comparative example is prepared by one-step blending, and the specific preparation method is as follows:
[0037] Ethanol (EtOH) and formamide (FA) are added to a beaker in a molar ratio of 1:2, and deionized water accounting for 40% by volume is added, and a certain amount of zinc acetate is added and mixed together, and heated and stirred at 80° C. to prepare a blended electrolyte, wherein the concentration of zinc acetate in the blended electrolyte is 1 mol / L.
[0038] Example 1
[0039] The wide temperature electrolyte provided in this embodiment is prepared by a two-step blending method, and the specific preparation method is as follows:
[0040] 1) Preparation of deep eutectic solution:
[0041] Ethanol (EtOH) and formamide (FA) were mixed at a molar ratio of 1:2 and heated at 80° C. to complete the complexation, thereby preparing a deep eutectic solution.
[0042] 2) Preparation of wide temperature electrolyte:
[0043] 6 mL of the deep eutectic solution was mixed with 4 mL of deionized water, and zinc acetate was added to the mixed solution. The mixture was stirred at room temperature to make it uniformly mixed to prepare a wide temperature electrolyte with EtOH:FA=1:2, wherein the concentration of zinc acetate in the wide temperature electrolyte was 1 mol / L.
[0044] Low temperature test: The macroscopic state of the electrolytes of Example 1 and Comparative Example 1 is compared. Figure 1 As shown, it can be seen that the wide temperature electrolyte of EtOH:FA=1:2 is liquid at -50°C, while the zinc acetate electrolyte is solid at -50°C. It can be seen that the wide temperature electrolyte of the present invention can improve the hydrogen bond network and inhibit the solidification of the electrolyte under low temperature conditions.
[0045] Zinc-zinc symmetric battery assembly: The electrolyte samples prepared in the above Example 1 and Comparative Examples 1 and 2 were respectively used to assemble zinc-zinc symmetric batteries. The zinc-zinc symmetric battery was assembled in air from a pair of metal zinc sheets, electrolyte, and diaphragm to form a button battery, wherein the diaphragm was a glass fiber diaphragm, and the amount of electrolyte used was 65 μL.
[0046] The electrochemical test of the zinc-zinc symmetrical battery was carried out on the NEWARE test system. The test temperatures were 50°C, 25°C, and -50°C, respectively. The test current and deposition amount were 1 mA / cm 2 、1mAh / cm 2 , the specific tests are as follows:
[0047] The wide temperature electrolyte of Example 1 is 1 mA / cm at 25°C. 2 The electrode surface and element distribution of the zinc ion battery after 10 cycles of current density are shown in Figure 2. Figure 2As shown, it can be seen that the electrode surface is smooth and flat, without dendrite growth. In the element distribution diagram, it can be seen that this is due to the adsorption of the deep eutectic solution on the electrode interface, which improves the electrode interface. The zinc acetate electrolyte of Comparative Example 1 was charged at 1 mA / cm at 25 °C. 2 The surface of the zinc ion battery electrode after 10 cycles of current density is as follows Figure 3 As shown, it can be seen that there are a large number of zinc dendrites on the electrode surface.
[0048] The comparative test curves of the cycle stability of the wide temperature electrolyte of Example 1 and the zinc acetate electrolyte of Comparative Example 1 at 50°C, 25°C and -50°C are shown in FIG. Figure 4 It can be seen that the wide temperature electrolyte has a cycle time of over 800 hours at 50°C, can stably cycle for over 1000 hours at 25°C, and can stably cycle for over 1400 hours at -50°C; while the cycle time of zinc acetate electrolyte is only 35 hours at 50°C, and only 42 hours at 25°C, and fails at -50°C due to coagulation of zinc acetate electrolyte. It can be seen that the electrolyte of the present invention effectively widens the operating temperature of zinc ion batteries and improves the cycle life of zinc ion batteries.
[0049] The cycle stability test curve of the blended electrolyte of Comparative Example 2 is shown in Figure 5 . It can be seen that the cycle time of the blended electrolyte at 50°C is only 75 hours, the cycle time at 25°C is only 300 hours, and the cycle time at -50°C is only 110 hours. Its performance is significantly reduced compared with the performance of the wide-temperature electrolyte of Example 1. This is because mixing the components for preparing the deep eutectic solution with deionized water at the same time will lead to a significant reduction in the number of bonds between the deep eutectics, which greatly reduces the ability of the wide-temperature electrolyte to improve the solution structure and electrode interface. Therefore, the preparation process of the wide-temperature electrolyte using a two-step blending method is irreplaceable.
[0050] Embodiment 2-4
[0051] Based on Example 1, three groups of examples were proposed by only changing the ratio of the raw materials (ethanol and formamide) of the deep eutectic solution, and electrochemical tests were performed according to the test method of Example 1. The molar ratios of ethanol and formamide in the three groups of examples and the test results are shown in Table 1.
[0052] Table 1
[0053]
[0054] From the data comparison in Table 1, it can be seen that the ratio of each component of the deep eutectic solution in the wide temperature electrolyte is the most critical, and changing its molar ratio will have a huge impact on the performance of the electrolyte. When the molar ratio of ethanol and formamide is gradually reduced from 1:0.5 to 1:4, the cycle stability shows a trend of first increasing and then decreasing, and the best effect is achieved when the molar ratio is 1:2.
[0055] Example 5
[0056] The wide temperature electrolyte provided in this embodiment is prepared by a two-step blending method, and the specific preparation method is as follows:
[0057] 1) The preparation of deep eutectic solution is:
[0058] Caprolactam (CPL) and glycerol (GLY) were mixed at a molar ratio of 0.7:1 and heated at 80° C. to complete the complexation, thereby preparing a deep eutectic solution.
[0059] 2) The preparation of the wide temperature electrolyte is as follows:
[0060] 6 mL of the deep eutectic solution was mixed with 4 mL of deionized water, and a certain amount of zinc acetate was added to the mixed solution. The mixture was stirred at room temperature to make it uniformly mixed to prepare a wide temperature electrolyte with CPL:GLY=0.7:1, in which the concentration of zinc acetate was 1 mol / L.
[0061] like Figure 1 In the low temperature test, the wide temperature electrolyte with CPL:GLY=0.7:1 is still liquid at -50℃.
[0062] The wide temperature electrolyte of Example 5 was subjected to electrochemical testing according to the method of assembling a zinc-zinc symmetrical battery in Example 1. The test results are shown in Figure 6 It can be seen that the wide temperature electrolyte has a cycle time of over 600 hours at 50°C, can stably cycle for over 700 hours at 25°C, and can stably cycle for over 800 hours at -50°C, which is also better than Comparative Example 1. It can be seen that the electrolyte of the present invention effectively widens the operating temperature of the zinc ion battery and improves the cycle life of the zinc ion battery.
[0063] Example 6
[0064] The wide temperature electrolyte provided in this embodiment is prepared by a two-step blending method, and the specific preparation method is as follows:
[0065] 1) The preparation of deep eutectic solution is:
[0066] Trifluoroacetamide (TFA) and ethylene glycol (EG) were mixed at a molar ratio of 1:4 and heated at 80° C. to complete the complexation, thereby preparing a deep eutectic solution.
[0067] 2) The preparation of the wide temperature electrolyte is as follows:
[0068] 6 mL of the deep eutectic solution was mixed with 4 mL of deionized water, and a certain amount of zinc acetate was added to the mixed solution. The mixture was stirred at room temperature to make it uniformly mixed to prepare a wide temperature electrolyte with TFA:EG=1:4, wherein the concentration of zinc acetate in the wide temperature electrolyte was 1 mol / L.
[0069] like Figure 1 In the low temperature test, the wide temperature electrolyte of TFA:EG=1:4 is still liquid at -50℃.
[0070] The deep eutectic solution of Example 6 was subjected to electrochemical testing according to the method of assembling a zinc-zinc symmetrical battery in Example 1. The test results are shown in FIG. Figure 7 It can be seen that the wide temperature electrolyte has a cycle time of over 600 hours at 50°C, can stably cycle for over 700 hours at 25°C, and can stably cycle for over 900 hours at -50°C.
[0071] Comparative Example 3
[0072] The wide temperature electrolyte provided in this comparative example is prepared as a wide temperature electrolyte using a deep eutectic additive prepared from acetonitrile (AN) and choline chloride (ChCl), and the specific preparation method is as follows:
[0073] Acetonitrile (AN) and choline chloride (ChCl) were mixed in a molar ratio of 1:2 and heated at 80°C to complete the complexation to prepare a deep eutectic solution. 6 mL of the deep eutectic solution was mixed with 4 mL of deionized water, and zinc acetate was added to the mixed solution, and stirred at room temperature to mix evenly to prepare a wide temperature electrolyte with AN:ChCl = 1:2, wherein the concentration of zinc acetate in the wide temperature electrolyte was 1 mol / L.
[0074] The prepared wide-temperature electrolyte was assembled into a zinc symmetric battery, and the amount of electrolyte used was 65 μL.
[0075] The cycle stability test curve of the wide temperature electrolyte of comparative example 3 is shown in Figure 8. It can be seen that the deep eutectic prepared from acetonitrile and choline chloride is prepared into a wide temperature electrolyte with a cycle time of only 90 hours at 50°C, a cycle time of only 130 hours at 25°C, and a cycle time of only 150 hours at -50°C. Although Comparative Example 3 also uses a deep eutectic solution to prepare a wide temperature electrolyte, the cycle performance of the assembled battery is significantly worse than that of Example 1. In addition, the applicant has also screened a variety of components for preparing deep eutectic solutions through a large number of experiments, and preferably selected the following deep eutectic solution materials with improved battery performance: the alcohol substance is selected from at least one of ethanol, ethylene glycol, and glycerol, and the amide substance is selected from at least one of caprolactam, formamide, and trifluoroacetamide. Any combination of the preferred alcohol substance and the amide substance can form a wide temperature electrolyte with excellent electrochemical properties, among which the wide temperature electrolyte prepared by combining ethanol (EtOH) and formamide (FA) has the best effect.
[0076] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.
Claims
1. A method for preparing a wide temperature electrolyte, characterized in that: The following steps are involved: S1, mixing an alcohol substance as a hydrogen bond donor and an amide substance as a hydrogen bond acceptor at a molar ratio of 1:0.2-1:20, and heating them to complete the complexation, so as to prepare a deep eutectic solution; wherein the alcohol substance is selected from at least one of ethanol, ethylene glycol, and glycerol, and the amide substance is selected from at least one of caprolactam, formamide, and trifluoroacetamide; S2. The deep eutectic solution is used as an electrolyte additive and mixed with deionized water, and zinc acetate is added to prepare a wide temperature electrolyte.
2. The method for preparing a wide temperature range electrolyte according to claim 1, characterized in that: In step S1, the temperature for heating the complexation reaction is 50-90°C.
3. The method for preparing a wide temperature range electrolyte according to claim 1, characterized in that: In step S1, the alcohol substance and the amide substance are mixed in a molar ratio of 1:
2.
4. The method for preparing a wide temperature range electrolyte according to claim 1, characterized in that: In step S2, the deep eutectic solution is added to deionized water at a volume percentage of 20-80%.
5. The method for preparing a wide temperature range electrolyte according to claim 1, characterized in that: The concentration of zinc acetate in the wide temperature range electrolyte is 0.2-4 mol / L.
6. A wide temperature electrolyte, characterized in that: The method is prepared by any one of claims 1 to 5.
7. Use of the wide temperature electrolyte according to claim 6 in aqueous zinc ion batteries.